2010
DOI: 10.1002/14651858.cd008147.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary vitamin E, selenium, cysteine and riboflavin for preventing kwashiorkor in preschool children in developing countries

Abstract: Background Protein Energy Malnutrition is an important cause of child morbidity and mortality in middle-and low-income countries. It has been suggested that excessive free radical activity may be responsible for the clinical manifestation of kwashiorkor. Antioxidants may be able to curb excessive free radical activity and prevent the development of kwashiorkor in susceptible children. Objectives To evaluate the benefits of supplementation of vitamin E, selenium, cysteine and riboflavin (alone or in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…These suggest that severely malnourished children require more cysteine as a precursor of glutathione (GSH) for anti-oxidant defense, as a building block for acute-phase proteins or mucins for an adequate immune response, or for gut mucosal proteins supporting to reverse the impaired gut function associated with severe acute malnutrition [ 21 ]. However, the only randomized controlled trial identified through a Cochrane Review [ 38 ] did not show any effects of supplementary antioxidant micronutrients including cysteine to Malawian children on the occurrence of kwashiorkor [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…These suggest that severely malnourished children require more cysteine as a precursor of glutathione (GSH) for anti-oxidant defense, as a building block for acute-phase proteins or mucins for an adequate immune response, or for gut mucosal proteins supporting to reverse the impaired gut function associated with severe acute malnutrition [ 21 ]. However, the only randomized controlled trial identified through a Cochrane Review [ 38 ] did not show any effects of supplementary antioxidant micronutrients including cysteine to Malawian children on the occurrence of kwashiorkor [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study identifies an inverse relationship between vitamin E and BMD in children and adolescents. Vitamin E supplementation during childhood may be helpful in issues like lung function, kwashiorkor, or liver disease [47][48][49]. Vitamin E supplementation for children and adolescents could not improve bone health or even damage bone health.…”
Section: Plos Onementioning
confidence: 99%